Investigating antibacterial activity of Satureja bachtiarica against coagulasenegative staphylococcus strains isolated from hospitalized patients in ICU,Tehran-Iran - Niloofar Shadalooei; Mehdi Goudarzi (Islamic Azad University, 2016)
Given the inappropriate use of antibiotics and prevalence of resistant bacteria, there is urgent need for antibacterial drugs that have fewer side effects than antibiotics. Satureja bachtiarica is a medicinal plant which had many uses in traditional medicine. In this research, the ethanol extract of leave of Satureja bachtiarica is tested on coagulase-negative staphylococcus strains. Materials and Methods: In this experimental study, after collecting and drying the plant extract, the ethanolic extract of the plant was extracted by soxhelet method. Then, the antibiotic resistance pattern of coagulase-negative staphylococcus strains to Cefoxitin, Tobramycin, Kanamycin, Amikacin, Gentamicin, was assessed. To evaluate the antibacterial activity, the minimum inhibitory concentration was assessed by using micro dilution broth method.The results of this study showed that the antimicrobial effect of Satureja extract is concentration dependent. The results of the antimicrobial activity of extracts, indicate that alcoholic extract in all dilutions have an antimicrobial effect on the coagulase-negative staphylococcus strains. The results show that coagulase-negative staphylococcus strains have highest resistance against Cefoxitin (0.39 mg/ml) and highest sensitivity to Amikacin (0.035 μl/ml). However, in 200 and 100 mg/ml concentrations the extract has higher antibacterial effect. According to the results of this study, ethanol extracts of leave of Satureja bachtiarica had growth inhibitory effect on coagulase-negative staphylococcus strains. Therefore this plant has the potential to be evaluated as an alternative or adjunct to antibiotics to treat coagulase-negative staphylococcus infections.